1999
DOI: 10.1146/annurev.phyto.37.1.447
|View full text |Cite
|
Sign up to set email alerts
|

THEDARKSIDE OF THEMYCELIUM: Melanins of Phytopathogenic Fungi

Abstract: Melanins are darkly pigmented polymers that protect organisms against environmental stress. Even when not directly involved in pathogenesis, fungal melanin is likely required by melanizing phytopathogens for survival in the environment. However, some phytopathogenic fungi that produce melanized appressoria for host invasion require appressorial melanogenesis for pathogenicity. Much less is known about the role melanins play in pathogenesis during infection by other phytopathogens that do not rely on appressori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
182
0
17

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(203 citation statements)
references
References 139 publications
4
182
0
17
Order By: Relevance
“…Silver also precipitates in hyphal septa, which suggests that septa also melanize, and silver precipitation does not occur near hyphal tips or in tricyclazole-treated hyphae or their septa. These findings are in agreement with previous research by Henson et al [21] and Butler and Lachance [17], who also observed the binding of Azure A dye to the septa of melanized hyphae of G. graminis. A copper sulfide-silver staining technique for fungal melanin detection in electron microscopy was further developed by Butler et al [3] and proved to be more efficient in labeling melanin produced in the black yeast Phaeococcomyces, in the G. graminis var.…”
Section: Melanin Biofilm Formations Involved In Sporogenesis Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…Silver also precipitates in hyphal septa, which suggests that septa also melanize, and silver precipitation does not occur near hyphal tips or in tricyclazole-treated hyphae or their septa. These findings are in agreement with previous research by Henson et al [21] and Butler and Lachance [17], who also observed the binding of Azure A dye to the septa of melanized hyphae of G. graminis. A copper sulfide-silver staining technique for fungal melanin detection in electron microscopy was further developed by Butler et al [3] and proved to be more efficient in labeling melanin produced in the black yeast Phaeococcomyces, in the G. graminis var.…”
Section: Melanin Biofilm Formations Involved In Sporogenesis Ofsupporting
confidence: 93%
“…The morphological variation of melanin assembly in different wood substrates reported in this research might explain the various chemical structures previously reported for fungal melanin [33,[39][40][41] as well as for the multiple genes identified in melanin biogenesis [21,[42][43][44][45]. Melanin deposits produced in vitro by T. versicolor in sugar maple tended to be attached to the wood cell walls, while in the same substrate pretreated with catechol, those bindings seemed sparse (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…However, future studies are needed to investigate this hypothesis. In many instances, microbial resistance to hostile environment is directly associated with dark pigmented polymers (Henson et al, 1999, Jacobson, 2000. Melanized cells are more resistant to hydrolytic enzymes, oxidative radicals, high temperatures, antifungals, and host defenses (Nosanchuck andCasadevall, 2003, Henson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Melanisation in fungi mostly seen in hyaline hyphae, sclerotia, appressoria, reproductive structures or conidia (Cordero and Casadevall 2017). Hyphal melanin is often found to be deposited as the outermost layer or internal layer in cell wall only with age or other stress (Bell and Wheeler 1986; Henson et al 1999; Butler et al 2001). Melanogenesis in pathogenic fungi plays a key role in pathogenesis in species such as Cryptococcus neoformans (Polacheck and Kwon-Chung 1988), Gaeumannomyces graminis var.…”
Section: Introductionmentioning
confidence: 99%
“…Melanogenesis in pathogenic fungi plays a key role in pathogenesis in species such as Cryptococcus neoformans (Polacheck and Kwon-Chung 1988), Gaeumannomyces graminis var. tritici, Magnaporthe grisea, Alternaria alternata, Colletotrichum lagenarium, Cochliobolus heterostrophus (Henson et al 1999), Paecilomyces variotti (Babitskaya et al 2000a), Rhizoctonia solani (Chen et al 2015) and Aspergillus spp. (Babitskaya et al 2000a; Schmaler-Ripcke et al 2009; Gonçalves et al 2012; Pal et al 2013).…”
Section: Introductionmentioning
confidence: 99%